Non-linear seismic response of arch dams with contraction joint opening and joint reinforcements. - Chuhan, Zhang (Earthquake engineering & structural dynamics.)
A comprehensive study of non-linear seismic response of arch dams with contraction joint opening and joint reinforcements has been conducted. A numerical model of contraction joint reinforcements is presented for optimization control of the joint opening. The objective of this control is to reduce the joint opening and expectantly to balance the sustained loads between the horizontal and the vertical components of the dam, thus avoiding an overstress in the cantilever while retaining the release of arch tensile stresses to some extent. Several parameter studies such as critical element size and required number of joints to be simulated for convergence are also performed. As an engineering application, a 292 m high arch dam (the Xiaowan arch dam) and the Big Tujunga dam are analysed in detail. The results demonstrate that the joint opening and the corresponding load transfer from the arch to cantilever components of the dam during strong earthquakes are substantial. It is also evident that by providing sufficient strength and reinforcement flexibility, the joint opening can be controlled to some extent. However, the stress redistribution due to reinforcement control is not sufficient to avoid the overstress in the cantilever for the Xiaowan arch dam. Thus, alternative measures are discussed.